Dynamic Analysis of an RCC Building Frame Considering Friction Damper Using Analysis Tool - Satish Baghel; Pradeep Nirmal; Anita Chaturvedi (International Journal of Scientific Research in Civil Engineering, 2025)
In this thesis, the seismic performance of reinforced cement concrete (RCC) structures with friction dampers is thoroughly examined and contrasted with that of RCC structures without dampers. Buildings situated on soil type III (soft soil), which is extremely vulnerable to seismic forces, and in Seismic Zone V, which has a zone factor of 0.36, are the subject of the study. By dispersing seismic energy through controlled frictional resistance, friction dampers—a type of passive energy dissipation device improve structural performance by lowering lateral vibrations. This study’s main goal is to evaluate how well friction dampers reduce seismic reactions and compare the outcomes with a traditional RCC model that does not include dampers. Key factors including base shear, tale drift, overturning moment, and shear force are used to conduct the analysis.